Development of cycling skills in 7- to 12-year-old children. (2nd October 2016) - Zeuwts, Linus; Vansteenkiste, Pieter; Cardon, Greet; Lenoir, Matthieu
ABSTRACT: Objective : Cycling is a complex skill consisting of motor skills such as pedalling, braking, and steering. Because the ability to perform cycling skills is based on the age-related development of the child, experience and age-related reference values are of interest in light of customized testing and training. Methods : One hundred thirty-eight children from the second (7–8 years), fourth (9–10 years), and sixth (11–12 years) grades performed a practical bicycle test consisting of 13 test items with specific points of interest. Moreover, age at onset of cycling, cycling to and from school, independent mobility, and minutes cycling per week were estimated using a parental questionnaire. Results: It is found that cycling skills are strongly related to age with 11- to 12-year-old children outperforming 7- to 8-year-old children for 11 test items and 9- to 10-year-old children for 8 test items. Conclusions : Next to age, age at onset of cycling also contributed to cycling skills. Therefore, our results suggest that cycling skills are associated with physical and mental maturation. Subsequently, age-related reference values are provided to customize testing and training.